Antara Netralitas dan Keberpihakan: Palang Merah di Jawa pada Masa Perang (1945–1949) - Rizky Eka Saputra (Lembaran Sejarah, 2022)
This research discusses about the role PMI (Indonesian Red Cross) and NERKAI (Nederlandsche Roode Kruis afdeeling Indonesië) in Java during Indonesian Independence War 1945-1949. As one of the most important institutions in wartime, the Indonesian Red Cross (PMI and NERKAI) was in a dilemmatic position. They had to obey the state for which they served, but on the other hand, they had to adhere to the fundamental principle of the International Red Cross. These dual functions have to be carried by the two Red Cross organizations, led them to abandon their neutrality. This study was designed to explain the reason why the two Red Cross organizations involved in the Indonesian Independence War abandoning their neutrality principle. This research found out, at least, four factors influenced the partiality actions of the Red Cross, first, the special status of the Red Cross in wartime; second, the unclear definitions of “Red Cross independent”; third, sentiment of the Indonesian nationalism; and fourth, the presence of militarism in the Red Cross.